Nasal microbiota transplantation: a gateway to novel treatments - Shekhar, Sudhanshu; Schwarzer, Martin; Dhariwal, Achal; Petersen, Fernanda Cristina (Trends in microbiology, 2025)
Two recent studies have highlighted the potential of nasal microbiota transplantation (NMT) to treat chronic rhinosinusitis (CRS). Here we evaluate these findings and propose that lessons from fecal microbiota transplantation (FMT) could guide NMT development, with possible implications for combating antimicrobial resistance in respiratory infections.
Keywords: fekální transplantace; mikrobiota; chronická nemoc; nasal microbiota; Microbiota; Chronic Disease; chronic rhinosinusitis; NMT; Nose; Rhinitis; dysbiosis; sinusitida; rýma; Sinusitis; lidé; Humans; nos; antimicrobial resistance; Fecal Microbiota Transplantation